Faktor-Faktor yang Memengaruhi Keputusan Membeli Majalah Elshinta - Beniko Kusumagiri; Nora H Pandjaitan; Anggraini Sukmawati (Institut Pertanian Bogor, 2016)
There are numerous magazines that discuss entrepreneurship and small and medium enterprises (SMEs) in Indonesia. The presence of these magazines indicated that the activities of SMEs are considered interesting and favored by the readers. The objectives of this research were to analyze the internal and external factors which affect the decision to purchase the Elshinta magazine and to analyze major factors that affect the decision in purchasing the Elshinta magazine. The results showed that internal and external factors were a challenge in managing the magazine,such as low competency of human resources, prices of raw materials increased and reading interest of Indonesian people were low. The results of the simple linear regression analysis using t-test showed that the price, product quality, promotion mix and brand image really influenced and partially positive to the decision to purchase the Elshinta magazine. The results of F-test showed that price, product quality, promotion mix and company’s brand image were simultaneously important and had real affects in increasing the decision in purchasing the Elshinta magazine. The results of the test analysis using the SPSS showed that there were positive and significant affects of variables i.e product quality, promotion mix and brand image on the decision to purchase the Elshinta magazine.